Ecophysiological characteristics of the nematophagous fungus, Plectosphaerella plurivora, with biocontrol potential on Nacobbus aberrans s.l. in tomato - Girardi, Natalia Soledad (2023)
The plant-parasitic nematode, Nacobbus sp., is responsible for significant economic losses in horticultural production centers in Argentina and other countries in America, alone or in combination with other biotic and abiotic factors. Although the genus’ distribution is restricted to the American continent, it has quarantine importance and is subject to international legislation to prevent its spread to other regions. The management of phytoparasitic nematodes using biological control strategies is a promising eco-compatible alternative, allowing for sustainability of the crop horticultural system. Firstly, this study ecophysiologically characterized Plectosphaerella plurivora SRA14, a strain with nematophagous activity on N. aberrans s.l. This fungal strain developed in vitro under a wide temperature range (20–30 °C), but the highest levels of water stress (Ψ: -7 and -10 Mpa; aW: 0.95 and 0.93) inhibited its growth. While the production of extracellular enzymes by this strain was low, P. plurivora SRA14 was able to develop in the rhizosphere and endorhizosphere of the tomato and basil crops without affecting the plant vigor parameters or producing phytotoxicity signs. Secondly, this study evidenced the biocontrol activity of P. plurivora SRA14 on N. aberrans s.l. populations in tomato, implanted into both sterile (artificially inoculated) and naturally infested soils via greenhouse pot experiments. The results of this work revealed for the first time the potential of P. plurivora SRA14 as a biological control agent of the phytoparasitic nematode N. aberrans s.l. in horticultural crops.